2015
DOI: 10.5937/sjm10-8095
|View full text |Cite
|
Sign up to set email alerts
|

Quality management tools applying in the strategy of logistics services quality improvement

Abstract: Quality improvement is one of the most popular strategy of the contemporary enterprises. Process improvement programs that do not refer directly to increase its competitive advantage, they are doomed to fail. Walmart, FedEx, McDonald's and other companies, which are struggling to have their products and services have always been of the high quality while maintaining competitive pricing, must continually

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Using the SERVQUAL model, Memić et al [30] showed that the users were not satisfied with the logistics services of a passenger transport company since all the dimensions had negative values regarding the difference between the observations and the expectations. Czajkowska and Stasiak-Betlejewska [31] used the SERVQUAL method to measure the expectations and the perceptions of the quality of logistics services in companies operating in Eastern Europe and showed that the quality of the services in the areas of "Empathy" and "Materiality" should be improved. Roslan et al [32] proposed a SERVQUAL-based model to measure the differences between customer satisfaction and desire in terms of the quality of logistics services provided by manufacturers in Iskandar, Malaysia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using the SERVQUAL model, Memić et al [30] showed that the users were not satisfied with the logistics services of a passenger transport company since all the dimensions had negative values regarding the difference between the observations and the expectations. Czajkowska and Stasiak-Betlejewska [31] used the SERVQUAL method to measure the expectations and the perceptions of the quality of logistics services in companies operating in Eastern Europe and showed that the quality of the services in the areas of "Empathy" and "Materiality" should be improved. Roslan et al [32] proposed a SERVQUAL-based model to measure the differences between customer satisfaction and desire in terms of the quality of logistics services provided by manufacturers in Iskandar, Malaysia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Inadequate quality issues have a key common feature, which is meeting product specifications and the customer satisfaction indicator [1]. In the case of services, quality is linked to customer preferences, and in the case of production, it relates to customer expectations [5]. Innovations in logistics processes have a positive impact on two-way work results [3].…”
Section: Introductionmentioning
confidence: 99%
“…Importance of quality management and its impact on the performance of businesses has been widely researched and plethora of literature is available on this topic (Ali, 2014;Czajkowska & Stasiak-Betlejewska, 2015;Fotopoulos & Psomas, 2010;Jaafreh & Al-abedallat, 2012;Nguyen, Phan & Matsui, 2018). Simultaneously many researchers, (Gavrea, Ilies & Stegerean, 2011;Karia & Wong, 2013;Karia, Wong, Asaari & Lai, 2015;Kraja & Osmani, 2015), have emphasized the importance of service competencies as a tool to get competitive advantage for better performance, but the direct impact of quality management practices on the integration capability of Logistics Service Providers (LSPs) is not duly researched.…”
Section: Introductionmentioning
confidence: 99%